4-(Methylamino)pyridine - Ng, S.W. (International Union of Crystallography, 2010)
The non-H atoms of the title compound, C(6)H(8)N(2), lie in a common plane (r.m.s. deviation = 0.034 angstrom). In the crystal, adjacent molecules are linked by intermolecular N-H center dot center dot center dot N hydrogen bonds into a zigzag chain running along the c axis.